Sedation Effect of Acepromazine and Butorphanol in Dopplervelocimetric Parameters in Great Abdominal Arteries and Femoral Artery in Dogs - Mello, Fabíola Peixoto da Silva; Torres, Verônica Noriega; Cunha, Renata Ferreira; Meirelles, Tatiane; Gouvêa, Aline Silva; Sanchotene, Niesca Goulart; Neuwald, Elisa Barp; Matheus, Juliana Pereira; Mello, Fernanda Bastos de; Mello, João Roberto Braga de (Acta Scientiae Veterinariae, 2016)
Background: Doppler ultrasound is a non-invasive diagnostic imaging technique that allows vascular anatomical and dynamics evaluation. Each artery has flow velocity profiles and different Doppler spectrum. The purpose of this study was to determine if sedation with acepromazine and butorphanol in dogs alters Doppler velocimetric values and diameter from abdominal aorta, celiac, mesenteric cranial, renal, external iliac and femoral arteries of healthy dogs. Materials, Methods & Results: Twenty healthy female dogs, aged 1 to 5 years, with body weight ranging from 10 to 25 kg, were evaluated with Doppler ultrasound in order to obtain: peak systolic velocity, end diastolic velocity, time average medium velocity, time average maximum velocity, resistive index, pulsatility index, and diameter from abdominal aorta, celiac, mesenteric cranial, renal, external iliac and femoral arteries. The same animals were sedated with acepromazine (0.02 mg/kg) and buthorphanol (0.4 mg/kg) and the same parameters were reevaluated. The heart rate was also measured. The study was approved by the Animal Ethics Committee of UFRGS, under the 25552 protocol, and the owners signed an informed consent form. Statistical analysis was performed with pared t test.The heart rate was statistically significant different, 98 ± 20.13 bpm before and 79 ± 17.74 after sedation. The exam was done before and after sedation in all selected vessels, except the celiac and cranial mesenteric artery, which were possible only in 35% and 45% respectively. All measured arteries exhibit difference in at least two of the analyzed parameters, except femoral artery, that only diameter was different. Discussion: Each vessel was selected because of its importance, and each of them has its own characteristic waveform. Changes in patterns of flow velocity of the celiac artery and mesenteric can help to determine the physiological condition of the gastrointestinal tract; in the case of renal arteries are associated with diseases involving parenchyma and; thrombosis in the aorta and the iliac and femoral arteries may be difficult to evaluate without the Doppler image. Examination of the AC and AMC before and after sedation not could be performed in all animals, maybe because the present work was carried out with only fasting requirement, without using dimethicone, and one of the difficulties encountered was the presence of gas in the gastrointestinal tract. Another factor that may have contributed to these findings is that the acute stress of containment and other environmental factors can cause release of vasopressin and leads to vasoconstriction of the splanchnic vascular bed. The dopplervelocimetric data found in celiac, mesenteric cranial, renal and femoral arteries in non-sedated animals was similar to what was described by other authors. Although all dogs demonstrated relaxation during the exam, this sedation protocol alters the values found with Doppler ultrasound in the selected vessels, except femoral artery, which caused only increase of diameter. The Doppler differences found can be a consequence of a decrease in heart rate associated with longer cycle length, and therefore, larger diastolic volume with vessels that stayed with same diameter, or in case of caudal abdominal aorta, that reduced the diameter. This study compared the dopplervelocimetric values to the ones described by other authors in non-sedated animals and demonstrated that although acepromazine and buthorphanol are a good option to sedate dogs to perform ultrasound exam, they alter the Doppler values from aorta abdominal, celiac, cranial mesenteric, renal, external iliac arteries and the femoral artery diameter.